Draft Annual Plan 1972-73 Part II Jammu and Kashmir - Planning Commission (Planning Commission, 1972)
The area of the State on the Indian side of the Cease Fire Line is 138992.1 sq. kms. According to the 1971 Census, the State has a total population of 46.15 lacs. Geophysically, the State can be divided into three distinct regions consisting of Jammu and Kashmir Divisions and Ladakh District.
Planning Department, Jammu and Kashmir Government